A conceptual model of perceived risk-based maintenance management for public schools - Mohd Dahari, Nurul Diyana; Mohammad Ali, Irwan; Khalil, Natasha; Abdul Wahab, Suriani Ngah (Academica Press Solutions, 2025)
The declining condition of public-school facilities is a serious concern, as poor maintenance not only affects safety but also impacts the overall learning experience for students. Many current maintenance practices do not effectively address the challenges of ageing infrastructure, such as performance issues, budget constraints, safety risks, and operational disruptions. These challenges highlight the need for a better approach to maintenance management. This research presents a new model called the perceived risk-based maintenance management (PRBMM) model, which helps prioritize maintenance tasks based on the risks associated with school facilities. The authors identify four key factors—performance, financial, safety, and operational risks—that influence how these risks are perceived. By focusing on these factors, the model offers a clear framework for improving maintenance in public schools. Implementing the PRBMM model is expected to lead to safer school environments, better facility performance, and more sustainable infrastructure. Moreover, this model can be used in various educational institutions and adapted for other sectors facing similar challenges. This study aims to fill a need in current maintenance practices by providing a straightforward framework that improves facility management and safety. The PRBMM model offers a practical solution that can be applied across different sectors needing effective maintenance management.